ANALYSIS OF TRIPLE PIPE HEAT EXCHANGER WITH TURBULATORS - et al., Dr. P.RAMESH KUMAR (International Journal of Advanced Science and Technology, 2019)
The heat exchangers (triple pipe heat exchangers) represent an important category of equipment in the petroleum refineries and are used for the purpose of evaporation, heating, pre-heating, cooling, condensation etc. The triple pipe heat exchanger is a modified constructive version of double pipe heat exchanger by adding an intermediate pipe. This intermediate pipe improves the heat transfer by increasing the heat area per unit length. The analysis of the heat transfer is made using experimental data obtained during the tests in a double and triple pipe heat exchanger. The flow rates of fluids, cold inlet and hot outlet temperatures of air is used in determining the performance of both heat exchangers. Principally, for both apparatus are calculated the overall heat transfer coefficients and the heat exchange surfaces. The presented results shows that triple pipe heat exchangers provide better heat transfer efficiencies compared to the double pipe heat exchangers.